PET Measures of Endogenous Opioid Neurotransmission Predict Impulsiveness Traits in Humans - Love, Tiffany M. (2009)
OBJECTIVE: The endogenous opioid system and μ-opioid receptors are known to interface environmental events, both positive (e.g., relevant emotional stimuli) and negative (e.g., stressors) with pertinent behavioral responses, regulating motivated behavior. Here we examined the degree to which trait impulsiveness, the tendency to act on cravings and urges rather than delaying gratification, is predicted by either baseline μ-opioid receptor availability or the response of this system to a standardized, experientially-matched stressor. METHOD: Nineteen (19) young healthy male volunteers completed a personality questionnaire (NEO PI-R) and positron emission tomography scans with the μ-opioid receptor selective radiotracer [(11)C]carfentanil. Measures of receptor concentrations were obtained at rest and during the receipt of an experimentally maintained pain stressor of matched intensity between subjects. Baseline receptor levels and stress-induced activation of μ-opioid neurotransmission were compared between subjects scoring above and below the population median of the NEO impulsiveness subscale and the orthogonal dimension, deliberation, expected to interact with it. RESULTS: High impulsiveness and low deliberation scores were associated with significantly higher regional μ-opioid receptor concentrations and greater stress-induced endogenous opioid system activation. Effects were obtained in regions involved in motivated behavior and the effects of drugs of abuse: prefrontal and orbitofrontal cortex, anterior cingulate, thalamus, nucleus accumbens and basolateral amygdala. Mu-opioid receptor availability, and the magnitude of stress-induced endogenous opioid activation in these regions accounted for 21 to 49% of the variance in these personality traits. CONCLUSIONS: Our data demonstrate that individual differences in the function of the endogenous μ-opioid system predicts personality traits that confer vulnerability or resiliency for risky behaviors, such as the predisposition to develop substance use disorders. These personality traits are also implicated in psychopathological states (e.g., personality disorders), where variations in the function of this neurotransmitter system may play a role as well.